TOURISM-LED GROWTH HYPOTHESIS AND ECONOMIC GROWTH IN KENYA - Yano, Justin; Matanda, Joshua (International Journal of Economics, 2021)
Purpose: The purpose of this study was to analyze tourism-led growth hypothesis in Kenya's economy. Materials and Methods: The descriptive research design was adopted. This study targeted international tourism receipts, employment, economies of scale and capital investments in tourism related economic activities that included hotels and food service activities, wholesale and retail trade, transport and information communication and travel agencies, entertainment and recreation in the period 1980 to 2019.The study used purposive sampling. a sample size of data for 40 years from 1980 to 2019 was used. The data were collected from KNBS, the World Bank and WTTC using a secondary data collection sheet. Using real GDP per capita as the dependent variable and international tourism receipts, tourism related employment, economies of scale and capital investments as the independent variables, the study used regression and vector error correction (VEC) to carry out the analysis. The analysis was systematic and begins with diagnostic tests that included Breusch-Godfrey Serial Correlation LM test, Breusch-Pagan-Godfrey test for homoscedasticity, Jarque-Bera normality test, VIF multi-collinearity test, Augmented Dickey Fuller unit root test and Johansen Co-integration test and finally the regression and the vector error correction analysis. Data analysis was done using E-views software. Results: The study results showed that international tourism receipts, tourism related employment and economies of scale positively influence real GDP per capita in both short run and long run equilibrium. Capital investments negatively affected real GDP per capita in the long run but had a positive effect in the short run equilibrium. Granger causality test presented a bi-directional causality between international tourism receipts, tourism related employment, economies of scale and capital investments and real GDP per capita. Unique contribution to theory, practice and policy: The country should enact policies that promote tourism related activities because the benefits derived from tourist expenditures positively influence the growth of the economy. Institutions such as Brand Kenya, Tourism Promotion Council, the Ministry of Tourism and recruitment of international tourism ambassadors should be strengthened to ensure more foreign tourists are attracted into the country.